2016
DOI: 10.1039/c6dt01817c
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable azobenzene-appended iridium(iii) complexes

Abstract: Iridium(iii) cyclometalated complexes have been used as models to study the effect that extended conjugation and substitution pattern has on the photochromic behavior of azobenzene-appended 2-phenylpyridyl (ppy) ligands. For this purpose four azobenzene-containing ppy ligands were synthesized. With these ligands, nine iridium(iii) complexes containing up to three appended azobenzenes were synthesized. Analysis of their photochromic behaviour by means of UV-vis and (1)H-NMR spectroscopy permitted us to conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…[Ir III (C^N) 2 (A) n ] + species where A is either two monodentate or one bidentate ligand(s) represent an important subclass of emissive materials, 34 and azobenzenes can themselves be weakly emissive. Freixa et al showed that [Ir III (C^N) 2 (A) n ] + complexes bearing cyclometallated 35 or bipyridyl appended 28 AZB units have negligible luminescence owing to competitive electron transfer from the mixed CT triplet to the azo group. The emission properties of cages C1 , C1-Me , C2 and C3 were determined in DCM solution, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[Ir III (C^N) 2 (A) n ] + species where A is either two monodentate or one bidentate ligand(s) represent an important subclass of emissive materials, 34 and azobenzenes can themselves be weakly emissive. Freixa et al showed that [Ir III (C^N) 2 (A) n ] + complexes bearing cyclometallated 35 or bipyridyl appended 28 AZB units have negligible luminescence owing to competitive electron transfer from the mixed CT triplet to the azo group. The emission properties of cages C1 , C1-Me , C2 and C3 were determined in DCM solution, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the photoisomerization dynamics is strongly influenced by the conjugation pathway and modified upon coordination of a metal to the azobenzene containing conjugated ligand, as previously demonstrated by Fillaut and coworkers for a series of Ruthenium(II) tris(bipyridine) complexes [16]. More recently Freixa and coworkers reported Iridium(III) cyclometalated complexes, in which the use of an aliphatic spacer unit between the azobenzene and the coordinating unit of the ligand allowed the electronic communication to be disrupted and the observation of photochromic properties for these coordination complexes [2].…”
Section: Photoisomerization Studiesmentioning
confidence: 74%
“…Of course, the photoinduced isomerization of azobenzene and its derivatives is one of the most and well-studied light driven processes. The location of the azobenzene unit in the ligands has A C C E P T E D M A N U S C R I P T been established as an important factor to influence the photochromic properties of azobenzene containing transition metal complexes [2][3][4][5]. The isomerization is assumed to take place from intraligand excited states localized on the azobenzene unit.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions are one of the most efficient tools to modify and enlarge the application range of phosphorescent emitters. ,, Thus, they have been employed to convert iridium­(III) complexes bearing cyclometalated 2-phenylpyridines or related ligands into emissive polymers and dendrimers . Freixa and co-workers have appended azobenzene moieties to the phenyl group, to study the influence of the extended conjugation and substitution on the photochromic properties of the resulting systems . Williams’ group has assembled multimetallic broad-band light emitters, through coupling of mononuclear bis-terpyridyl complexes with extended conjugation …”
Section: Resultsmentioning
confidence: 99%